New Media and Political Awareness among Young People - الناصري سلام خطاب (ALBAHITH ALALAMI, 2015)
This study seeks to answer urgent questions about the role of new media that have emerged recently, such as the Internet and social networking sites and information services through mobile and others to increase awareness among young people, especially university students. during a field study that took place on a sample of students in the Department of Media at the University of Petra Kingdom of Jordan during the second semester in 2013 in the study the researcher finds increased attention and follow-up by young people for many of the world events and regional and local communities through exposure to a number of new media; in the forefront of the Internet and increase the level of awareness and interests young people do many of the events at the level of social networking sites or in the exchange of information and dialogue with others as part of a new technical and communicative opens new doors in terms of media and communication and its role at the level of the individual and society and its importance in influencing public opinion.